Low-temperature heat capacity of fullerite C₆₀ doped with deuteromethane - Bagatskii, M.I.; Sumarokov, V.V.; Dolbin, A.V. (Физика низких температур, 2012)
The heat capacity C of fullerite doped with deuteromethane (CD₄)₀.₄(C₆₀) has been investigated in the temperature interval 1.2–120 K. The contribution CD₄ ΔC of the CD₄ molecules to the heat capacity C has been separated. It is shown that at T ≈ 120 K the rotational motion of CD₄ molecules in the octahedral cavities of the C₆₀ lattice is weakly hindered. As the temperature decreases to 80 K, the rotational motion of the CD4 molecules changes from weakly hindered rotation to libration. In the range T = 1.2–30 K CD₄ ΔC is described quite accurately by the sum of contributions from the translational and librational vibrations and tunneling rotation of the CD₄ molecules. The contribution of tunneling rotation to the heat capacity CD₄ ΔC T( ) is dominant below 5 K. The effect of nuclear-spin conversion of the CD₄ molecules upon the heat capacity has been observed and the characteristic times of nuclear spin conversion between the lowest levels of the A- and T-species of the CD₄ molecules at T < 5 K have been estimated. A feature observed in the curve CD₄ ΔC T( ) near T = 5.5 K is most likely a manifestation of a first-order phase transition in the orientational glass of the solution.